Analysis Of Sayyid Qutub's Thought And Tafsir Fî Zhilâl Al-Qur'an In The Discipline Of Tafsir Science - Haq, Fakhri Iqomul; Hasan, Abdurrohim; Kamaludin, Ahmad (Civilization Research: Journal of Islamic Studies, 2025)
This research aims to analyze Sayyid Qutub's Thought and Tafsir Fî Zhilâl Al-Qur'an in the Discipline of Tafsir Science. The research used in this study is library research which is descriptive-analytic in nature. This research model is qualitative research. The method used in this research also uses thematic method. Based on the results of the study, the writing of Tafsir fi Zilal al-Qur'an was motivated by the social and political circumstances experienced by Sayyid Qutub in his time. Sayyid Qutub lived in a period when the Arab and Islamic worlds were undergoing significant changes, including modernization, colonialization, and political movements. Sayyid Qutb critically looked at the condition of Muslims and tried to interpret the Qur'anic messages in the context of modern times. He sought to revive the spirit of pure Islam and fight for social justice based on the teachings of the Qur'an. Fî Zhîlâl al-Qur`ân is Sayyid Qutub's attempt to convey a deep understanding of the Qur'an to Muslims, as well as inviting them to think critically about the social and political realities they face. Through this tafsir, Sayyid Qutub also wants to inspire Muslims to move in the struggle towards a more just society based on Islamic values.